Electronic and reactivity characteristics of CL-20 covalent chains and networks: a density functional theory study. Issue 30 (17th July 2018) - Gimaldinova, Margarita A.; Maslov, Mikhail M.; Katin, Konstantin P.
Abstract : The low-dimensional nanostructures built with CL-20 units were studied in order to investigate the possibility of creating covalent CL-20 crystals. Abstract : The covalent low-dimensional nanostructures built with CL-20 units by means of CH2 molecular bridges are examined in order to investigate the possibility and probability of creating covalently bonded arrays with CL-20 fragments as building blocks. In this way, various CL-20 oligomers were constructed including simple and double chains as well as surface-like networks. Density functional theory at the PBE0/6-311G(d, p) level indicates that CL-20 covalent systems become more thermodynamically stable as their effective size and dimensionality increase. Thus, the formation of bulk covalent CL-20 solids may be energetically favorable, and such structures may possess high kinetic stability compared with the CL-20 molecular crystals. However, at the bulk limit, such structures can be attributed to wide-bandgap semiconductors, and electron transfer within the CL-20 chain or network may occur only through doping or substitution with additional functional groups. In addition, chemical reactivity indices such as chemical hardness and softness, chemical potential, electronegativity, and electrophilicity were calculated and analyzed.